Molecular signals for Late Tertiary/Early Quaternary range splits of an Eurasian steppe plant: Clausia aprica (Brassicaceae) - Franzke, Andreas (Molecular ecology, 2004)
Several vegetation belts stretch continuously from Europe to Asia, taiga and steppe being most prominent. Numerous plant species within these belts share a conspicuous distribution area, which is longitudinally contracted or disrupted approximately along longitude 70° E. To date no hypothesis for this intriguing distribution pattern has been put forward. We detected molecular footprints in the contemporary genetic composition in nuclear DNA (ITS1, ITS2) and chloroplast DNA (trnL-trnF spacer region) of the steppe element Clausia aprica (Brassicaceae) providing evidence for a severe longitudinal range split and genetic differentiation east of the Ural Mountains about 1 million years ago caused by Quaternary climatic oscillations. Clausia aprica provides the first phylogeographical analysis on the intraspecific evolution of an Eurasian steppe plant.